2022
DOI: 10.1111/all.15259
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial and sensory mechanisms of nasal hyperreactivity

Abstract: + current/channel; K CA , Ca 2+ -gated K + current/ channel; K V , voltage-gated K + current/channel; NHR, nasal hyperreactivity; NO, nitric oxide; ORAI1, calcium release-activated calcium channel protein 1; STIM1, stromal interaction molecule 1; TREK1, TWIK-related K+ channel 1; TRPV1, transient receptor potential channel vanilloid 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 103 publications
0
20
0
Order By: Relevance
“…Airway epithelial cells not only form a physical barrier against inhaled particles, but also recruit and activate other effector cells by producing antimicrobial peptides, chemokines, and cytokines to scavenge pathogenic insults (55). Studies have shown that the expression of TJ proteins such as claudin-1, occludin and ZO-1 is significantly reduced in patients with asthma and upper respiratory diseases such as nasal polyps and chronic rhinosinusitis (56,57). Claudin-18 expression, a TJ protein required for maintaining the integrity of the airway epithelial permeability, was also lower in asthmatics compared to healthy controls (58,59).…”
Section: Epithelial Barrier Hypothesismentioning
confidence: 99%
“…Airway epithelial cells not only form a physical barrier against inhaled particles, but also recruit and activate other effector cells by producing antimicrobial peptides, chemokines, and cytokines to scavenge pathogenic insults (55). Studies have shown that the expression of TJ proteins such as claudin-1, occludin and ZO-1 is significantly reduced in patients with asthma and upper respiratory diseases such as nasal polyps and chronic rhinosinusitis (56,57). Claudin-18 expression, a TJ protein required for maintaining the integrity of the airway epithelial permeability, was also lower in asthmatics compared to healthy controls (58,59).…”
Section: Epithelial Barrier Hypothesismentioning
confidence: 99%
“…More recently, neuropeptides have been reported to be involved in ILC2 activation at mucosa sites 7 . Rare neuroendocrine cells such as tuft cells and pulmonary neuroendocrine cells (PNECs) from the airway epithelial layer can secrete peptides and sense hypoxia, as well as environmental stimuli 8–10 . ILC2s selectively express the neuromedin U receptor 1 (NMUR1), and the combined expression of NMU and IL‐25, but not NMU alone, strongly promotes murine ILC2s activation induced by the house dust mite (HDM) in a cell‐intrinsic manner 11,12 .…”
Section: Pathomechanisms In Armentioning
confidence: 99%
“…7 Rare neuroendocrine cells such as tuft cells and pulmonary neuroendocrine cells (PNECs) from the airway epithelial layer can secrete peptides and sense hypoxia, as well as environmental stimuli. [8][9][10] ILC2s selectively express the neuromedin U receptor 1 (NMUR1), and the combined expression of NMU and IL-25, but not NMU alone, strongly promotes murine ILC2s activation induced by the house dust mite (HDM) in a cell-intrinsic manner. 11,12 Following OVA inhalation, murine lung PNECs release calcitonin gene-related peptide (CGRP), which can further enhance IL-5 production from ILC2s in the presence of both IL-25 and IL-33.…”
Section: New Cognition Of Ilc2s In Armentioning
confidence: 99%
“…A protective film composed of secretions from goblet cells, known as the mucus blanket of the nasal epithelium, forms the first barrier in nasal immunity by trapping and removing harmful substances such as dust particles, bacteria, and viruses 48–52 . The dysfunction of the nasal epithelium due to ciliary beat disorders or abnormal goblet cell secretion leads to mucous deposition and inflammation in CRS 53–56 …”
Section: Effect Of Hypoxia On Structural Cellsmentioning
confidence: 99%
“…[48][49][50][51][52] The dysfunction of the nasal epithelium due to ciliary beat disorders or abnormal goblet cell secretion leads to mucous deposition and inflammation in CRS. [53][54][55][56] Hypoxia may play a key role in the pathogenesis of CRS via nasal epithelial cells. It was previously suggested in a study by Hwang et al that the proliferation of nasal mucosal epithelial cells is inhibited under hypoxia.…”
Section: Nasal Epithelial Cellsmentioning
confidence: 99%